Correction: Analysis of dialkyl urine metabolites of organophosphate pesticides by a liquid chromatography mass spectrometry technique. Issue 36 (10th September 2018) - Sinha, Sukesh Narayan; Reddy, B. Venkat; Vasudev, Kasturi; Vardhana Rao, M. Vishnu; Ahmed, M. Noor; Ashu, Shaik; Kumari, Alka; Bhatnagar, Vijay
Abstract : Correction for 'Analysis of dialkyl urine metabolites of organophosphate pesticides by a liquid chromatography mass spectrometry technique' by Sukesh Narayan Sinha et al., Anal. Methods, 2014, 6, 1825–1834.